2010
DOI: 10.2139/ssrn.2039119
|View full text |Cite
|
Sign up to set email alerts
|

New Immigrants' Assessments of Their Life in Canada

Abstract: La version française de cette publication est disponible (n o 11F0019M au catalogue, n o 322). Note of appreciation Canada owes the success of its statistical system to a long-standing partnership between Statistics Canada, the citizens of Canada, its businesses, governments and other institutions. Accurate and timely statistical information could not be produced without their continued cooperation and goodwill. Standards of service to the public Statistics Canada is committed to serving its clients in a promp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…This new found independence and the belief that education can enhance one's bargaining position within traditional households likely play a role in their children's academic pursuits, particularly among their daughters (Zhou and Bankston ). Further, many immigrants cite greater opportunities for their children as a key motivation for moving to Canada (Houle and Schellenberg ). Thus, immigrants who migrated for this reason are more likely to be supportive of their daughters pursuing higher education.…”
Section: Discussionmentioning
confidence: 99%
“…This new found independence and the belief that education can enhance one's bargaining position within traditional households likely play a role in their children's academic pursuits, particularly among their daughters (Zhou and Bankston ). Further, many immigrants cite greater opportunities for their children as a key motivation for moving to Canada (Houle and Schellenberg ). Thus, immigrants who migrated for this reason are more likely to be supportive of their daughters pursuing higher education.…”
Section: Discussionmentioning
confidence: 99%
“… Statistics Canada does not provide information on the further possible selectivity of the dropout, and there are hardly any publications that discuss this issue. An exception is a paper by Houle and Schellenberg (2010) in which it is shown that attrition is not related to the level of education and the occupational status of the respondent, nor is it related to the degree of satisfaction with the life in Canada. Still, it could be that attrition is selective on other variables. …”
mentioning
confidence: 99%
“…For instance, Chow () finds that satisfaction is positively correlated with friendships among Hong Kong adolescent immigrants to Canada. Similarly, Houle and Schellenberg () detect a negative relationship between satisfaction with life in Canada and having little or no contact with friends. Those who report positive contact with neighbors and friends and those participating in religious services see their lives in the host country more positively.…”
Section: Methodsmentioning
confidence: 99%
“…Looking at the relationship between pre‐migration expectations and post‐migration experiences of immigrants from Russia to Finland, Mähönen and colleagues () found that the more actual experiences exceeded the expectations, the better were immigrants’ life satisfaction and general mood. Similarly, Houle and Schellenberg () found that younger immigrants to Canada tended to assess their lives more positively compared to older immigrants, and those with higher levels of education are less likely to be satisfied with their lives in Canada compared to immigrants with lower educational attainment due to higher expectations among the older and less educated immigrants.…”
Section: Literature Reviewmentioning
confidence: 99%